Morbid Obesity Is Associated With Adverse Clinical Outcomes in Acute Pancreatitis: A Propensity‐Matched Study. (November 2015) - Krishna, Somashekar G; Hinton, Alice; Oza, Veeral; Hart, Phil A; Swei, Eric; El‐Dika, Samer; Stanich, Peter P; Hussan, Hisham; Zhang, Cheng; Conwell, Darwin L
Abstract : OBJECTIVES: Morbid obesity may adversely affect the clinical course of acute pancreatitis (AP); however, there are no inpatient, population‐based studies assessing the impact of morbid obesity on AP‐related outcomes. We sought to evaluate the impact of morbid obesity on AP‐related clinical outcomes and health‐care utilization. METHODS: The Nationwide Inpatient Sample (2007–2011) was reviewed to identify all adult inpatients (≥18 years) with a principal diagnosis of AP. The primary clinical outcomes (mortality, renal failure, and respiratory failure) and secondary resource outcomes (length of stay and hospital charges) were analyzed using univariate and multivariate comparisons. Propensity score‐matched analysis was performed to compare the outcomes in patients with and without morbid obesity. RESULTS: Morbid obesity was associated with 3.9% (52, 297/1, 330, 302) of all AP admissions. Whereas the mortality rate decreased overall (0.97%→0.83%, P <0.001), it remained unchanged in those with morbid obesity (1.02%→1.07%, P =1.0). Multivariate analysis revealed that morbid obesity was associated with increased mortality (odds ratio (OR) 1.6; 95% confidence interval (CI) 1.3, 1.9), prolonged hospitalization (0.4 days; P <0.001), and higher hospitalization charges (5, 067; P <0.001). A propensity score‐matched cohort analysis demonstrated that the primary outcomes, acute kidney failure (10.8 vs. 8.2%; P <0.001), respiratory failure (7.9 vs. 6.4%; P <0.001), and mortality (OR 1.6, 95% CI 1.2, 2.1) were more frequent in morbid obesity. CONCLUSIONS: Morbid obesity negatively influences inpatient hospitalization and is associated with adverse clinical outcomes, including mortality, organ failure, and health‐care resource utilization. These observations and the increasing global prevalence of obesity justify ongoing efforts to understand the role of obesity‐induced inflammation in the pathogenesis and management of AP.